3(x+9)=-3(4x-5)+6x

Simple and best practice solution for 3(x+9)=-3(4x-5)+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+9)=-3(4x-5)+6x equation:



3(x+9)=-3(4x-5)+6x
We move all terms to the left:
3(x+9)-(-3(4x-5)+6x)=0
We multiply parentheses
3x-(-3(4x-5)+6x)+27=0
We calculate terms in parentheses: -(-3(4x-5)+6x), so:
-3(4x-5)+6x
We add all the numbers together, and all the variables
6x-3(4x-5)
We multiply parentheses
6x-12x+15
We add all the numbers together, and all the variables
-6x+15
Back to the equation:
-(-6x+15)
We get rid of parentheses
3x+6x-15+27=0
We add all the numbers together, and all the variables
9x+12=0
We move all terms containing x to the left, all other terms to the right
9x=-12
x=-12/9
x=-1+1/3

See similar equations:

| 4x-30=7(-2x+2+10 | | 2x-4=3x=6 | | 9-b=11 | | 3(x-2)=(6x-12)÷3 | | 6|4y-8=-2 | | a+7/3=-3 | | −6x−16=2x | | 8h=8+10h | | 28+21m-14=35+14-14m | | 7x-2+1=5x+7 | | 3x+2=-x+34 | | 7(2n-3)=119 | | 28+21m-14=35+14-24m | | -5(9+y)=20-3+6y | | (3x)=(2x)+65 | | -4+4x=90 | | (2x-12)+(3x-15)=180 | | 4p-2=26 | | 3x+9=9x+43 | | -3=a+15 | | (2x+10)=46= | | 4(g+8)=7-+4g | | -(4x-4)=24 | | 6x-2+6x=-74 | | 6.35x+9=40.3225+3x | | 9+8p=-3p | | 10=15c | | 53=3b-1 | | -5x+10+4x=17 | | 4.29x-0.692=11.749 | | -(1-n)=3(2n-2) | | 6k+15=27 |

Equations solver categories